Bromido(2,4,6-trimethylphenyl)mercury(II) - Frank Meyer-Wegner (Acta Crystallographica Section E, 2012)
Molecules of the title compound, [HgBr(C9H11)], are located on a crystallographic twofold rotation axis. Due to the molecular symmetry, the HgII atom is linearly coordinated by the ipso-C of the mesityl group and the Br atom. In the crystal, molecules lie in planes parallel to (001).